2005
DOI: 10.1103/physreve.71.016102
|View full text |Cite
|
Sign up to set email alerts
|

Universal non-Gaussian velocity distribution in violent gravitational processes

Abstract: We study the velocity distribution in spherical collapses and cluster-pair collisions by use of N -body simulations. Reflecting the violent gravitational processes, the velocity distribution of the resultant quasistationary state generally becomes non-Gaussian. Through the strong mixing of the violent process, there appears a universal non-Gaussian velocity distribution, which is a democratic (equal-weighted) superposition of many Gaussian distributions (DT distribution). This is deeply related with the local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…For velocity distributions in the sphere, we examine onedimensional velocity distribution functions combining alldirectional components of the velocity distribution [32]. The velocity distribution function f (v) is first averaged over 30 simulations.…”
Section: Parameters For Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For velocity distributions in the sphere, we examine onedimensional velocity distribution functions combining alldirectional components of the velocity distribution [32]. The velocity distribution function f (v) is first averaged over 30 simulations.…”
Section: Parameters For Simulationsmentioning
confidence: 99%
“…In these systems, the velocity distributions are non-Gaussian [31][32][33], especially in quasiequilibrium states and metastable states. For example, Iguchi et al proposed universal non-Gaussian velocity distributions for a spherical collapse in a violent gravitational process of a collisionless stage (t < τ r ) [32], and Carvalho et al indicated that the q parameter in the Tsallis distribution depends on the age of open stellar clusters [33]. (Here τ r represents the relaxation time, which is driven by the two-body encounter [1]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations of collapse and relaxation processes of self-gravitating collisionless systems, similar to galaxies, are useful in identifying their general trends, such as density and anisotropy profiles. Two studies of the velocity distribution function of these systems by means of numerical simulations were performed, showing that the velocity distribution of the resultant quasi-stationary states generally becomes non-Gaussian (Iguchi et al 2005;Hansen et al 2006). …”
Section: Non-gaussian Velocity Distributionsmentioning
confidence: 99%
“…We discuss the equilibrium properties of the Self Gravitating Ring (SGR) model, a toy model for self gravitating systems. Whereas we mainly present here its equilibrium properties, we stress that this system is very interesting also from a dynamical point of view, as it shows a number of out of equilibrium quasi-stationary states [31,32].…”
Section: Figurementioning
confidence: 99%